2014
DOI: 10.1161/circulationaha.114.009990
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammatory Disorders and Risk of Type 2 Diabetes Mellitus, Coronary Heart Disease, and Stroke

Abstract: Background-This study sought to evaluate whether risks of diabetes mellitus and cardiovascular disease are elevated across a range of organ-specific and multisystem chronic inflammatory disorders. Methods and Results-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
236
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(252 citation statements)
references
References 50 publications
(50 reference statements)
11
236
1
4
Order By: Relevance
“…70 In the general population, high-sensitivity (hs) CRP and fibrinogen both provide additive predictive ability for cardiovascular disease although the incremental addition beyond clinical risk factors is relatively modest. In subjects without known cardiovascular disease, markers of cardiac injury and stress, such as hs-cardiac troponin (cTn) I, ST2, GDF-15, and N-terminal-proBNP (NT-proBNP; Table 3) are associated with an increased risk of death and adverse cardiovascular events, particularly heart failure, with a lesser effect on the risk of coronary heart disease events.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…70 In the general population, high-sensitivity (hs) CRP and fibrinogen both provide additive predictive ability for cardiovascular disease although the incremental addition beyond clinical risk factors is relatively modest. In subjects without known cardiovascular disease, markers of cardiac injury and stress, such as hs-cardiac troponin (cTn) I, ST2, GDF-15, and N-terminal-proBNP (NT-proBNP; Table 3) are associated with an increased risk of death and adverse cardiovascular events, particularly heart failure, with a lesser effect on the risk of coronary heart disease events.…”
Section: Inflammationmentioning
confidence: 99%
“…70 In the general population, high-sensitivity (hs) CRP and fibrinogen both provide additive predictive ability for cardiovascular disease although the incremental addition beyond clinical risk factors is relatively modest. 71,72 More recent, but less clearly established, emerging predictors of coronary artery disease in the general population include TNFRII, 73 EN-RAGE, 74 and soluble CD14.…”
Section: Inflammationmentioning
confidence: 99%
“…34 A recent study of a large primary care database (UK Clinical Practice Research Datalink), including participants with psoriasis and related disorders, bullous skin disorders, ulcerative colitis, Crohn disease, inflammatory arthritis, systemic autoimmune diseases, and systemic vasculitis, showed an increased risk of CVD with chronic inflammatory disease, calling for the importance of clinical management of such conditions to reduce cardiovascular risk. 35 Chronic inflammation may also be involved in the development of atherosclerosis in persons without rheumatologic disorders. In the JUPITER (Justification for the Use of Statins in Primary Prevention: An Intervention Trial Evaluating Rosuvastatin) trial of apparently healthy persons without hyperlipidemia but with elevated C-reactive protein levels (a marker of inflammation), rosuvastatin significantly reduced the incidence of major cardiovascular events including stroke.…”
Section: Bang Et Al Nontraditional Risk Factors For Ischemic Stroke 3573mentioning
confidence: 99%
“…Two inception cohorts using the Clinical Practice Research Datalink have provided opposing results; Parisi et al [25] found no increased risk of major cardiovascular events while Degran et al [26] reported an increased risk for severe psoriasis patients.…”
Section: Introductionmentioning
confidence: 99%